2010
DOI: 10.2307/41219165
|View full text |Cite
|
Sign up to set email alerts
|

Are Young French Jobseekers of Ethnic Immigrant Origin Discriminated against? A Controlled Experiment in the Paris Area

Abstract: This study uses the findings of a correspondence testing in order to assess the potential discrimination at job access level against young people of ethnic origin from the underprivileged suburbs of the Paris area (Ile-de-France

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…In the case of Europe, the results are similar for discrimination against Asian‐sounding names in Czech and German labor markets (Bartoš, Bauer, Chytilová, & Matějka, ). In line with our study, Duguet et al () and Edo and Jacquemet () provide results of discrimination on the French labor market against applicants with Arabic‐sounding names. Alongside these studies that investigate the effect of the names, some studies address the effect of a foreign nationality on labor market discrimination.…”
Section: Literature Reviewsupporting
confidence: 92%
See 3 more Smart Citations
“…In the case of Europe, the results are similar for discrimination against Asian‐sounding names in Czech and German labor markets (Bartoš, Bauer, Chytilová, & Matějka, ). In line with our study, Duguet et al () and Edo and Jacquemet () provide results of discrimination on the French labor market against applicants with Arabic‐sounding names. Alongside these studies that investigate the effect of the names, some studies address the effect of a foreign nationality on labor market discrimination.…”
Section: Literature Reviewsupporting
confidence: 92%
“…First, we are only interested on the impact of an applicant’s perceived foreign origin. This personal trait has been shown by Duguet et al () and Edo and Jacquemet () to induce strong name‐based discrimination in the same geographical area as our study (the greater Paris area). Second, our indication of foreign origin is based on text only, while Acquisti and Fong () also manipulate the background image across fictitious applicants.…”
Section: Literature Reviewsupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, in industries and jobs in which workers are in contact with clients, employers may discriminate against residentially segregated workers to satisfy the perceived prejudices of their clients (Holzer & Ihlanfeldt, 1998). A recent French study used the findings of a correspondence test that assessed potential discrimination to job access (Duguet et al, 2011). The authors found a 'negative' effect for being a nationality other than French.…”
Section: Mechanisms Of Neighbourhood Effectsmentioning
confidence: 99%